Plasma membrane proteome of adhesion‐competent endometrial epithelial cells and its modulation by Rab11a. Issue 1 (18th November 2019) - Kakar‐Bhanot, Ruchi; Brahmbhatt, Krupanshi; Kumar, Vipin; Suryawanshi, Amol R.; Srivastava, Sanjeeva; Chaudhari, Uddhav; Sachdeva, Geetanjali
Abstract: Human endometrial epithelium (EE) is composed of a multitude of proteins, amongst which those localized on the plasma membrane [plasma membrane proteins (PMPs)] are of critical relevance in the early stages of implantation. Evidence supports the key role of few PMPs in implantation. However, many remain unidentified, as efforts have not been made till date to generate the plasma membrane proteome of human EE cells, using a gel‐free approach. This study presents a protein catalog of the PMP enriched fraction of Ishikawa cell line; often used as an in vitro model for embryo‐adhesive EE. Liquid chromatography with tandem mass spectrometry identified 3, 598 proteins. Of these, 1, 963 proteins were annotated for their membrane localization. Of 1, 963 proteins, 1, 321 were found to have a transmembrane domain and 43 proteins had glycophosphatidylinositol (GPI) anchor. Extensive data mining revealed endometrial expression of 943 proteins reported in humans and/or rodents. Further, quantitative alterations were observed in the plasma membrane proteome on the perturbation of intracellular trafficking. Silencing of Rab11a (known for its role in plasma membrane organization) expression caused alteration in the abundance of 74 proteins. Caveolin‐1 and EpCAM levels were reduced whereas Rab4a abundance increased in the PMP extracts of Rab11a deficient cells, compared with control cells. Briefly, the study reports the identity of several novel plasma membrane‐localized proteins. A major spin‐off of the study is the identification of novel proteins trafficked by Rab11a to the plasma membrane. Targeted analysis of novel PMPs may reveal their specific roles in endometrial receptivity and implantation. Abstract : The study provides a catalog of plasma membrane‐associated proteins of endometrial epithelial cells which can be explored for their specific roles in endometrial functions and dysfunctions.